Puma (Puma concolor) diet and habitat use in south-west New Mexico - Bernard, Kelly Monica Tandi (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
The puma (Puma concolor) is a wide-ranging large felid species occupying an extensive geographic range throughout North and South America, and site-specific research on their diet is important for local management. Like other large felids, puma diet may differ between sexes due to size dimorphism, and between seasons due to changes in prey vulnerability and availability. This study assessed the influence of sex and season on puma diet in south-west New Mexico in terms of prey species and prey size categories. Pumas specialised on mule deer and elk throughout the year, and killed a range of other species of different sizes. The diet of the smaller female puma was nested within the diet of males, supporting the size-nested strategy. The effect of puma sex on prey species and size categories was independent of season, and vice versa, and the probability of a female making a medium-sized kill such as mule deer was higher than for males, while the probability of an extra-large kill such as elk was substantially greater for males. The probability of pumas killing either mule deer or elk in each season was similar, and greater than other species categories. Additionally, individual puma strongly influenced all prey species and size categories killed. The results from this study concur with previous findings on the importance of mule deer and elk in puma diet, and suggest that puma predation may also impact a number of other species, particularly smaller herbivores like collared peccary, and mesocarnivores such as skunks.
Keywords: Puma Food -- New Mexico; Puma -- Habitat -- New Mexico; Puma -- Nutrition -- New Mexico; Puma -- Conservation -- New Mexico; Carnivorous animals -- New Mexico; Red deer; Elk; Mule deer; Ungulates